2023
DOI: 10.1055/s-0043-1777285
|View full text |Cite
|
Sign up to set email alerts
|

Solvents Influence 1H NMR Chemical Shifts and Complete 1H and 13C NMR Spectral Assignments for Florfenicol

Wan-Ting Ai,
Wei-Ke Su,
Feng Su

Abstract: Florfenicol (FFC) is an important and widely used veterinary drug, and its structure has been characterized by nuclear magnetic resonance (NMR) spectroscopy. The study aimed to investigate the influences of solvent type, solvent concentration, and temperature on the chemical shifts of the 1H NMR of FFC. The results showed that different types of solvents significantly affected the chemical shifts, especially the chemical shifts of 2-H, 3-H, 5-H, and the active protons. When DMSO-d 6 is used as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…4d ). These results can be explained by the increase in the overall polarity of the solvent mixture caused by addition of constant proportions of acid, in accordance with the literature 34 36 . Quantum-chemical calculations (GFN2-xTB (6.4.1)) provide insights into the most stable conformation of the BPy unit (cis or trans) of (Z) 1 -H + (Supplementary Fig.…”
Section: Resultssupporting
confidence: 91%
“…4d ). These results can be explained by the increase in the overall polarity of the solvent mixture caused by addition of constant proportions of acid, in accordance with the literature 34 36 . Quantum-chemical calculations (GFN2-xTB (6.4.1)) provide insights into the most stable conformation of the BPy unit (cis or trans) of (Z) 1 -H + (Supplementary Fig.…”
Section: Resultssupporting
confidence: 91%
“…35 The increase of chemical shift in 1 H indicates a decrease in the electron density of the furan ring. 36,37 This observation suggested that the Lewis acid ZnCl 2 coordinated with the furan ring and electrons were transferred from the furan ring to Zn 2+ . The chemical shift of 1 H in Na-FA showed a similar trend after adding ZnCl 2 (Fig.…”
Section: Resultsmentioning
confidence: 99%